Impact of behavioral and psychological symptoms of Alzheimer’s disease on caregiver outcomes - Kanokporn Pinyopornpanish; Atiwat Soontornpun; Tinakon Wongpakaran; Nahathai Wongpakaran; Surat Tanprawate; Kanokwan Pinyopornpanish; Angkana Nadsasarn; Manee Pinyopornpanish (Scientific Reports)
Abstract This study was to determine the prevalence of behavioral and psychological symptoms of dementia (BPSD) and its association with dementia severity and to explore the association between specific BPSD and caregiver stress, burden, and depression. A cross-sectional study involving the interviewing of the primary caregivers of patients with Alzheimer’s disease (AD) was conducted. Multivariable analysis was used to analyze the associations between specific symptoms of BPSD and caregiver outcomes. A total of 102 AD patients (age 79.4 ± 7.9 years, 70.6% female) and their caregivers were included. Nearly 46% had moderate-to-severe AD. Nearly all patients (99.0%) had at least one BPSD. Apathy was among the most common symptoms (74.5%), and hallucination was the only symptom associated with severity of AD (p = 0.017). After adjustment, agitation was associated with Patient Health Questionnaire-9 (PHQ-9) and Zarit Burden Interview (ZBI-22) (p = 0.021 and 0.007, respectively); sleep disorders were associated with only PHQ-9 (p = 0.049). In conclusion, the BPSD, especially agitation and sleep disorders, can give rise to difficulties for both patients and their caregivers. The prevalence of BPSD is high (99.0%), and the symptoms can start early. Routine screening of BPSD in all AD patients is advocated.